Resveratrol alleviates bleomycin-induced lung injury in rats - ERCAN, FERİHA; ŞENER, GÖKSEL (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2007)
Antioxidant therapy may be useful in diseases with impaired oxidant-antioxidant balance such as pulmonary fibrosis. This study was designed to examine the effects of resveratrol, an antioxidant agents, against bleomycin-induced pulmonary fibrosis and oxidative damage. Wistar albino rats were administered a single dose of bleomycin (5 mg/kg; via the tracheal cannula) followed by either saline or resveratrol (10 mg/kg; orally) for 14 days. The effect of resveratrol on pulmonary oxidative damage was studied by cell count and analysis of cytokine levels (TGF-beta, TNF-alpha, IL-1 beta and IL-6) in the bronchoalveolar lavage fluid (BALF) and biochemical measurements of malondialdehyde (MDA), an end product of lipid peroxidation; glutathione (GSH), a key antioxidant; and myeloperoxidase (MPO) activity, an index of neutrophil infiltration, in the lung tissue. Bleomycin-induced lung fibrosis was determined by lung collagen contents and also microscopically. Bleomycin caused a significant decrease in lung GSH, which was accompanied with significant increases in MDA level, MPO activity, and collagen contents of the lung tissue concomitant with increased levels of the pro-inflammatory mediators and cell count in BALF. On the other hand, resveratrol treatment reversed all these biochemical indices as well as histopathological alterations induced by bleomycin. The results demonstrate the role of oxidative mechanisms in bleomycin-induced pulmonary fibrosis, and resveratrol, by its antioxidant properties, ameliorates oxidative injury and fibrosis due to bleomycin. Thus, an effective supplement with resveratrol as an adjuvant therapy may be a very promising agent in alleviating the side effects of bleomycin, an effective chemotherapeutic agent. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: bleomycin; resveratrol; fibrosis; cytokine; lipid peroxidation; glutathione; IDIOPATHIC PULMONARY FIBROSIS; ORAL N-ACETYLCYSTEINE; MYELOPEROXIDASE ACTIVITY; MECHANISMS; DAMAGE; INFLAMMATION; PROTECTION; CYTOKINES; MELATONIN; SEPSIS